Industrial training report: Suruhanjaya Bebas Tatakelakuan Polis (IPCC) / Muhammad Amirul Aizad Roslan - Roslan, Muhammad Amirul Aizad (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The practical experience gained during my eight-week industrial training at Suruhanjaya Bebas Tatakelakuan Polis (IPCC). The internship aimed to bridge academic knowledge and real-world application, offering hands-on involvement in tasks related to review website, make an animation video, and make a poster. My primary responsibilities included developing a video for corporate using application Powtoon. Other than that create a poster for corporate using Canva and review and compare website. Through these tasks, I enhanced my skills in Canva, Powtoon, design skill, Problem-Solving Skills, and Content Skills. The report also reflects on the development of key soft skills such as teamwork, communication, and time management, which were integral to successfully completing assignments and collaborating with colleagues. These experiences have provided a comprehensive understanding of integrity operations within an organization, preparing me for future roles in the field and helping me to grow both professionally and personally.